COVID-19 related epigenetic changes and atopic dermatitis: An exploratory analysis - Zhenwei Tang, MD; Yu Chen, MBBS; Yuzhen Ouyang, MBBS; Yu Peng, MD, PhD; Xiaoyong Man, MD, PhD (World Allergy Organization Journal)
Background: While epidemiological data suggest a connection between atopic dermatitis (AD) and COVID-19, the molecular mechanisms underlying this relationship remain unclear. Objective: To investigate whether COVID-19-related CpGs may contribute to AD development and whether this association is mediated through the regulation of specific genes’ expression. Methods: We combined Mendelian randomization and transcriptome analysis for data-driven explorations. Results: Among the 172 CpGs -associated with COVID-19 infection, merely 3 of them exhibited significant impacts on the risk of AD, including cg04543273, cg11916609, and cg10636246. In the following analysis of the causal effects of CpGs and their related gene expression, cg04543273 inhibited LMAN2 expression. However, there was not a significant impact of cg11916609 and cg10636246 on the expression of their corresponding genes. Besides, transcriptome analysis suggested that LMAN2 expression was significantly upregulated among the COVID-19-infected population, and LMAN2 expression was obviously correlated with Type 2 helper cells across different post-infection time points. Conclusion: Overall, this study provides new insights of the COVID-19-related onset and exacerbation of AD-COVID-19-related epigenetic changes and their regulatory impact on transcription. A novel role of LMAN2 was proposed in the relationship between viral infection and AD. More studies are warranted to further explore the mechanism of LMAN2-related immunopathology.